2007
DOI: 10.1111/j.1461-0248.2007.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Global negative vegetation feedback to climate warming responses of leaf litter decomposition rates in cold biomes

Abstract: Whether climate change will turn cold biomes from large long-term carbon sinks into sources is hotly debated because of the great potential for ecosystem-mediated feedbacks to global climate. Critical are the direction, magnitude and generality of climate responses of plant litter decomposition. Here, we present the first quantitative analysis of the major climate-change-related drivers of litter decomposition rates in cold northern biomes worldwide. Leaf litters collected from the predominant species in 33 gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
392
5
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 413 publications
(408 citation statements)
references
References 58 publications
10
392
5
1
Order By: Relevance
“…Other studies have shown that increasing temperature results in the lengthening of the growing season and improved productivity (Kimball et al, 2006;Barichivich et al, 2013). These effects may partly counteract the negative effects of climate warming (Cornelissen et al, 2007). Additionally, Kumar et al (2013) suggested that the impact of climate change on soil microbes in Arctic regions may be impossible to predict.…”
Section: Comparisons With Previous Resultsmentioning
confidence: 99%
“…Other studies have shown that increasing temperature results in the lengthening of the growing season and improved productivity (Kimball et al, 2006;Barichivich et al, 2013). These effects may partly counteract the negative effects of climate warming (Cornelissen et al, 2007). Additionally, Kumar et al (2013) suggested that the impact of climate change on soil microbes in Arctic regions may be impossible to predict.…”
Section: Comparisons With Previous Resultsmentioning
confidence: 99%
“…For example, needles, hardwood leaves, grass, and forbs showed different mass loss rates, 10.0, 15.6, 21.0, and 39.0 %, respectively, under snow cover in a balsam fir (A. balsamea) forest over a 6-month snow-covered season (Taylor and Jones 1990). Moreover, the decomposition rate of different plant types is generally in the order of forbs [ graminoids [ deciduous shrubs [ evergreen shrubs (Cornelissen 1996;Cornelissen et al 2007). In general, our results are consistent with the above studies to some degree, as the litter of deciduous shrubs decomposed significantly faster than that of evergreen shrubs and trees.…”
Section: Discussionmentioning
confidence: 99%
“…For example, graminoids and herbs have been gradually replaced by shrubs in alpine ecosystems (Cornelissen et al 2007;Baptist et al 2010), leading to alterations of plant community structure and species composition (Lenoir et al 2008), as well as plant litter decomposition (Gavazov 2010).…”
mentioning
confidence: 99%
“…In this approach, litters of multiple species are incubated simultaneously, in the same litter matrix ('litterbed'), so that mass loss rates can be interpreted directly in terms of species' litter 'decomposability'. After the first study of this kind on leaf litter in a temperate flora (Cornelissen 1996), this common garden approach made some key advances at Abisko Research Station in sub-Arctic Sweden under the guidance and directorship of Terry Callaghan (Quested et al 2003;Cornelissen et al 2007;Freschet et al 2012c) and eventually in many biomes of the world. Together these studies revealed that the range of variation in leaf litter decomposition rates among species within sites worldwide was generally greater than the range of variation of a given litter type across climatic zones from the Arctic to the Tropics (Cornwell et al 2008).…”
Section: Common Garden Experimentsmentioning
confidence: 99%